2006
DOI: 10.1056/nejmoa062032
|View full text |Cite
|
Sign up to set email alerts
|

Return of Chloroquine Antimalarial Efficacy in Malawi

Abstract: Chloroquine is again an efficacious treatment for malaria, 12 years after it was withdrawn from use in Malawi. (ClinicalTrials.gov number, NCT00125489 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
297
5
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(324 citation statements)
references
References 27 publications
21
297
5
1
Order By: Relevance
“…This sharp reduction in the level of in vivo CQ resistance may be explained by the 2005 antimalarial treatment policy change from CQ to artemether-lumefantrine or artesunate-amodiaquine as first lines treatments for acute uncomplicated malaria in Nigeria, although, chloroquine has not been completely withdrawn, despite the change in drug policy. It has been argued that the withdrawal of CQ or SP as first line treatment for uncomplicated malaria in other disease endemic settings of Africa has led to the reemergence of drug sensitive Plasmodium falciparum [8][9][10]. The fact that in-vitro CQ resistance (54%) is higher than in-vivo resistance (38%), may be attributed to immunopotentiation of antimalarial drugs by patients immunity, which would have helped older patients (>5years of age) clear drug CQ resistant parasites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sharp reduction in the level of in vivo CQ resistance may be explained by the 2005 antimalarial treatment policy change from CQ to artemether-lumefantrine or artesunate-amodiaquine as first lines treatments for acute uncomplicated malaria in Nigeria, although, chloroquine has not been completely withdrawn, despite the change in drug policy. It has been argued that the withdrawal of CQ or SP as first line treatment for uncomplicated malaria in other disease endemic settings of Africa has led to the reemergence of drug sensitive Plasmodium falciparum [8][9][10]. The fact that in-vitro CQ resistance (54%) is higher than in-vivo resistance (38%), may be attributed to immunopotentiation of antimalarial drugs by patients immunity, which would have helped older patients (>5years of age) clear drug CQ resistant parasites.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier report [8] has demonstrated the return of CQ susceptible parasites in Malawi soon after the country switched from CQ to SP as the first line therapy for malaria. Furthermore, a recent clinical trial in Malawi also confirmed that CQ had excellent clinical efficacy, 12 years after it was removed from use [9,10 ]. It is therefore necessary to understand the molecular basis of resistance to already available antimalarial drugs such as CQ, and explore the potentials of the information generated in improving the potency and rational for developing effective drug combinations.…”
Section: Introductionmentioning
confidence: 99%
“…This mutation in a putative transporter gene is well-associated with chloroquine resistance in P. falciparum (5). The MSS-HTA was compared with a standard allele-restricted PCR (ARPCR) in clinical samples from Malawi, a country where standard PCR analyses and a recent clinical trial have suggested that chloroquine-resistant malaria has disappeared (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Pfcrt est également impliqué dans la baisse de sensibilité du parasite à l'amodiaquine et à la quinine [41,42]. Dans les zones où les allèles de résistance ne sont pas fixés, on observe une augmentation de la fréquence de l'allèle sauvage après abandon de la chloroquine [43,44]. L'analyse de ce locus renseigne sur la pression médicamenteuse exercée au sein des populations.…”
Section: Approches Méthodologiquesunclassified